Goal 4 of Sustainable Development Goals (SDG) and India’s Education Policy: A Comparison (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Education and literacy serve as crucial benchmarks for a society, significantly contributing to the socio-economic progress of an entire nation. Recognizing education as the cornerstone of human resource development, the Government of India’s New Education Policy (NEP) has undergone a consultative process. In order to adapt to the evolving needs of quality education, innovation, and research in today’s world, NEP strives to transform India into a center of knowledge by providing students with skill enhancement and advancement opportunities, including ICT and vocational training.India has made remarkable strides in implementing the Education for All initiative. Various key programs and policies have been launched to ensure that all children between the ages of six and fourteen have access to free and compulsory education as a Fundamental Right. Initiatives like Sarva Siksha Abhiyan (SSA) and Right to Education (RTE) have played a crucial role in boosting the education system in India. While there has been a significant improvement in primary education enrollment rates nationwide, there are still challenges that need to be tackled. This paper primarily focuses on the current strategies adopted by India to align with Goal 4 of the Sustainable Development Goals (SDGs) in the Indian context, by incorporating them into the development of the New Education Policy and its positive impact on achieving quality education, as highlighted in SDG 4. It also delves into the education achievements at primary, secondary, and tertiary levels in India, as well as the major obstacles hindering quality education and accessibility in the education sector.